Reposisi Lembaga Perpajakan - AG Subarsono (Magister Administrasi Publik, 2004)
Tax is one of the most crucial areas of government, especially in promoting national revenue and regulating the national economy. According to the current sociopolitical context, the effective use of tax is expected to overcome economic crisis and to reduce the local government's financial burden in implementing local autonomy. Based on empirical data, tax ratio in Indonesia is still lower than other neighboring countries, such as: Singapore, Malaysia, and Thailand. Therefore Indonesia urgently needs to reform its' tax organization (Direktorat Jendral Pajak). Besides that, the position of tax organization under the Department of Finance is improper due to the differingfunctions of the tax organization and the Department of Finance. The Department of Finance formulates national budget and maintains public asset while the tax organization collects money and ensures citizen compliance. This article argues about the importance of reforming the tax organization becoming a national tax agency directly under the President and thus having more autonomy and power, as well as a reduction of political intervention from other departments.